Clinical characteristics of fatal and recovered cases of coronavirus disease 2019 in Wuhan, China: a retrospective study - Deng, Yan; Liu, Wei; Liu, Kui; Fang, Yuan-Yuan; Shang, Jin; Zhou, Ling; Wang, Ke; Leng, Fan; Wei, Shuang; Chen, Lei; Liu, Hui-Guo (Chinese medical journal, 2020)
The 2019 novel coronavirus has caused the outbreak of the acute respiratory disease in Wuhan, Hubei Province of China since December 2019. This study was performed to analyze the clinical characteristics of patients who succumbed to and who recovered from 2019 novel coronavirus disease (COVID-19). Clinical data were collected from two tertiary hospitals in Wuhan. A retrospective investigation was conducted to analyze the clinical characteristics of fatal cases of COVID-19 (death group) and we compare them with recovered patients (recovered group). Continuous variables were analyzed using the Mann-Whitney U test. Categorical variables were analyzed by χ test or Fisher exact test as appropriate. Our study enrolled 109 COVID-19 patients who died during hospitalization and 116 recovered patients. The median age of the death group was older than the recovered group (69 [62, 74] vs. 40 [33, 57] years, Z = 9.738, P < 0.001). More patients in the death group had underlying diseases (72.5% vs. 41.4%, χ = 22.105, P < 0.001). Patients in the death group had a significantly longer time of illness onset to hospitalization (10.0 [6.5, 12.0] vs. 7.0 [5.0, 10.0] days, Z = 3.216, P = 0.001). On admission, the proportions of patients with symptoms of dyspnea (70.6% vs. 19.0%, χ = 60.905, P < 0.001) and expectoration (32.1% vs. 12.1%, χ = 13.250, P < 0.001) were significantly higher in the death group. The blood oxygen saturation was significantly lower in the death group (85 [77, 91]% vs. 97 [95, 98]%, Z = 10.625, P < 0.001). The white blood cell (WBC) in death group was significantly higher on admission (7.23 [4.87, 11.17] vs. 4.52 [3.62, 5.88] ×10/L, Z = 7.618, P < 0.001). Patients in the death group exhibited significantly lower lymphocyte count (0.63 [0.40, 0.79] vs. 1.00 [0.72, 1.27] ×10/L, Z = 8.037, P < 0.001) and lymphocyte percentage (7.10 [4.45, 12.73]% vs. 23.50 [15.27, 31.25]%, Z = 10.315, P < 0.001) on admission, and the lymphocyte percentage continued to decrease during hospitalization (7.10 [4.45, 12.73]% vs. 2.91 [1.79, 6.13]%, Z = 5.242, P < 0.001). Alanine transaminase (22.00 [15.00, 34.00] vs. 18.70 [13.00, 30.38] U/L, Z = 2.592, P = 0.010), aspartate transaminase (34.00 [27.00, 47.00] vs. 22.00 [17.65, 31.75] U/L, Z = 7.308, P < 0.001), and creatinine levels (89.00 [72.00, 133.50] vs. 65.00 [54.60, 78.75] μmol/L, Z = 6.478, P < 0.001) were significantly higher in the death group than those in the recovered group. C-reactive protein (CRP) levels were also significantly higher in the death group on admission (109.25 [35.00, 170.28] vs. 3.22 [1.04, 21.80] mg/L, Z = 10.206, P < 0.001) and showed no significant improvement after treatment (109.25 [35.00, 170.28] vs. 81.60 [27.23, 179.08] mg/L, Z = 1.219, P = 0.233). The patients in the death group had more complications such as acute respiratory distress syndrome (ARDS) (89.9% vs. 8.6%, χ = 148.105, P < 0.001), acute cardiac injury (59.6% vs. 0.9%, χ = 93.222, P < 0.001), acute kidney injury (18.3% vs. 0%, χ = 23.257, P < 0.001), shock (11.9% vs. 0%, χ = 14.618, P < 0.001), and disseminated intravascular coagulation (DIC) (6.4% vs. 0%, χ = 7.655, P = 0.006). Compared to the recovered group, more patients in the death group exhibited characteristics of advanced age, pre-existing comorbidities, dyspnea, oxygen saturation decrease, increased WBC count, decreased lymphocytes, and elevated CRP levels. More patients in the death group had complications such as ARDS, acute cardiac injury, acute kidney injury, shock, and DIC.